P51 Inadequate compensation by glutamine synthetase and increased glutaminase activity contributes to hyperammonaemia in cirrhosis. (16th November 2010) - Jover, M; Noiret, L; Habtesion, A; Balasubramaniyan, V; Sharifi, Y; Romero-Gomez, M; Davies, N; Jalan, R
Abstract : Introduction: In cirrhosis, the function of the urea cycle is compromised which leads to accumulation of ammonia. In this situation, ammonia metabolism is regulated by glutamine synthetase (GS) and glutaminase (GA) making them important therapeutic targets. The relative contributions of these enzymes in the different organs in regulating ammonia metabolism in cirrhosis are unclear. Aim: To study the protein expression and activity of glutamine synthetase (GS) and glutaminase (GA) enzymes in the different organs in a model of chronic liver disease (bile duct ligation: BDL). Method: Ten male Sprague–Dawley rats were studied (260.7±10.57)g: 4 sham operated, and 6 following bile duct ligation (BDL). We measured plasma levels for: ammonia and standard biochemical markers. Expression of GS and GA were determined by Western-blotting (described as % of sham expression) and activity by end point methods in liver, kidney, gut, muscle, lung and frontal cortex (brain). Results: Plasma ammonia was increased in BDL rats vs. Sham (45.97±14.72 vs 106.2±59.10) μmol/l). The most important organs for GS activity were the liver > lung = frontal cortex > muscle > kidney = gut. In cirrhosis, liver GS activity is reduced by 7 fold (62.61±8.29 SHAM vs 8.98±2.67* BDL). The most important organs for GA function in disease were: lung (0.70±1.4 SHAM vs 4.19±2.24* BDL) > kidney (1.24±0.09 SHAM vs 1.68±0.58* BDL) > gut (0.43±0.14 SHAM vs 1.14±0.51* BDL) (activities expressed as mIU/mg protein; *P<0.05). Gut Liver Kidney Muscle Lung Frontal cortex Brain SHAM GS (0.78+0.67) (62.61+8.29) (0.87+1.24) (1.75+0.48) (2.98+4.26) (2.74+1.14) GA (0.43+0.14) (1.84+0.58) (1.24+0.09) (0.37+0.14) (0.70+1.4) (0.61+0.30) BDL GS (0.84+0.84) (8.98+2.67)* (0.86+0.78) (1.92+0.63) (2.15+3.14) (3.22+0.35) GA (1.14+0.51)* (0.52+0.16)* (1.68+0.58)* (0.38+0.11) (4.19+2.24)* (0.63+0.20). Conclusion: Inadequate compensation by GS and increased GA activity account for hyperammonemia observed in cirrhosis. For the first time, these data indicate the importance of the lung in regulating ammonia metabolism through GS and also GA, activities of both of which are increased in cirrhosis. In order to reduce ammonia levels in cirrhosis, it would be advantageous for novel drugs to target GS stimulation and Glutaminase inhibition simultaneously.